Pengaruh Konsentrasi Pupuk Cair Limbah Tempe Terhadap Pertumbuhan Dan Hasil Tanaman Selada Romaine (Lactuca sativa L. var. longifolia): The Effect Of Tempe Waste Liquid Fertilizer Concentration On The Growth And Yield Of Romaine Lettuce (Lactuca sativa L. var. longifolia) - Vera Purnama; Tita Kartika Dewi; Lusiana; Hamdan Drian A; Nine Wahyuni; Rohdewi (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
The objective of this study was to assess the effect of varying amounts of liquid tempeh waste fertilizer on the growth and yield of romaine lettuce (Lactuca sativa L. var. longifolia). This study will be conducted in Gabus Kulon Village, Langgen Wetan District, Gabus Wetan Regency, Indramayu Regency, between August and October 2024. A straightforward Randomized Group Design (RAK) will be employed for this experimental setup. There will be four distinct treatments in this study, each replicated six times, with each treatment comprising six experimental plants and three samples taken from each plot. The treatments will include the tempe waste liquid fertilizer applied at different levels: P0 (control), P1 (30% concentration), P2 (60% concentration), and P3 (90% concentration). Findings from this study indicated that the application of different concentrations of tempe waste liquid fertilizer significantly affected the growth parameters of the plants, including height, leaf count, length of the leaves, and the fresh weight of the romaine lettuce, with the optimal concentration being 30% (P1), which resulted in the highest fresh weight of the plants at 24.56 grams. Keywords: Liquid Organic Fertilizer (POC), Liquid Tempeh Waste, Romaine Lettuce.